The American Heritage children's dictionary - Houghton Mifflin Company (Boston : Houghton Mifflin, 2003)
A dictionary designed especially for children in grades three through six, featuring over 34,000 alphabetically arranged entries, each with a pronunciation key and part of speech indicator, and includes illustrations, notes, a thesaurus, grammar helps, and other resources.
6.4.
6.4
3-6
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries; English language -- Dictionaries